Quantifying leaf litter production, decomposition, and nutrient release in cacao plantations in southwest Nigeria - Oyedele, O. (University of Ibadan, 2021)
Nutrient cycled from litterfall plays an important role in sustaining the fertility status in cacao (Theobroma cacao L.) plantations. However, the role of macrofauna in regulating the rate of decomposition and nutrient release remains uncertain despite its importance in litter decomposition and nutrient release. The study was carried out to assess the quantity and seasonal pattern of annual litterfall production in low-shade cacao plantations found in Southwestern Nigeria and also to determine the effects of macrofauna on the rate of cacao leaf litter decomposition and nutrients release. Field studies were conducted in three locations for 13 months, and the study was a factorial experiment laid out in a randomized complete block design with two replicates; position, sampling dates, and incubation were used as factors. Litterbags and wooden frames were used to study the effects of macrofauna on the rate of decomposition and nutrient release. The results of this study revealed that litterfall production in the study sites was subject to seasonal variation. Total annual litterfall production in the study sites ranged from 3.50 to 7.71 Mg DM ha-1 yr-1. Macrofauna significantly (p≤0.001) increased the rate of decomposition and nutrient release, but the rate of decomposition was strongly regulated by litter quality. The rates of nutrients release were in the following order Nitrogen>Potassium>Phosphorus. The nutrients release from cacao litter would play a significant role in the nutrition of the cacao tree.